Actinic keratosis – definition, aetiopathogenesis and therapeutical approach - Placek, Waldemar; Markiewicz, Agnieszka; Zając, Natalia; Bzdawski, Maciej (Dermatology Review/Przegląd Dermatologiczny, 2013)
Actinic keratosis is a skin condition that has been intriguing to dermatologists throughout the ages. Both the definition and the hypotheses on the aetiopathogenesis underwent several modifications. In 1869, for the first time actinic keratosis was described. Later the scientists noticed the impact of sun exposure on the development of this disease. Recent years have brought a breakthrough in the molecular aspect of aetiopathogenesis of KA. Together with the better understanding of the aetiopathogenesis of the disease new therapeutic approaches have developed dynamically. Today doctors have the possibility to choose the most accurate method depending on the clinical manifestation. The authors present both topical and surgical therapeutic methods, the well-known old ones as well as the brand new ones.